Comprehensive rehabilitation of patients of reproductive age with precancerous pathology of the cervix after organ saving surgeons - A.I. Rybin (Publishing House TRILIST, 2021)
The frequency of cervical dysplasia (cervical neoplasia) in the population is up to 5%, and in the structure of cervical diseases - 17-20%. Malignant transformation of the multilayered squamous epithelium is observed in almost 30% of patients with cervical dysplasia. The main surgical method of treatment of these conditions is diathermoconization of the cervix. But quite often patients have complaints in the late postoperative period. Comprehensive rehabilitation of patients of reproductive age with precancerous pathology of the cervix should include early restoration of sexual, reproductive and social functions of women. Research objective: to study the clinical effectiveness of the drug Femiclean (dequalinium chloride) in the comprehensive rehabilitation of patients with precancerous pathology of the cervix after organ-sparing surgery. Materials and methods. The first (main) group included 25 patients who, on the background of traditional treatment (broad diathermoconization of the cervix) for 6 days before and 12 days after treatment were treated with vaginal suppositories once a day Femiclean. The second (control) group consisted of 25 patients who underwent traditional treatment (broad diathermoconization of the cervix) with iodine-containing vaginal suppositories. Results. In patients of reproductive age with precancerous pathology of the cervix, who applied the developed concept of management in the postoperative period, the recurrence rate was probably lower; the epithelialization time was significantly higher than in women of the control group. The epithelialization time of the cervix in patients who used Femiclean vaginally in the pre- and postoperative period was 7.8 days faster compared to women who used standard vaginal drugs. The drug of domestic production Femiclean, according to our data, is well tolerated by patients and does not cause side effects. Conclusions. The developed complex rehabilitation of reproductive aged patients with precancerous pathology of the cervix after organ-sparing surgery has shown high clinical efficiency in comparison with traditional treatment this pathology.